Internet Marketing for Entrepreneurs: Using Web 2.0 Strategies for Success - Payton, Susan (Business Expert, 2012)
Don’t know a blog from a tweet? After reading this book, you’ll not only understand these terms, you’ll be able to use them to market your business! This book is your introduction to Marketing 2.0. It shows you how to leverage new media tools like Facebook, Twitter, blogs, and the New Media Press Release to grow your business and your followers, as well as how to participate in meaningful conversations with past, present, and future customers. The book will also identify strategies you can implement immediately to grow awareness of your brand online.